Measuring the reactivity of commercially available zero-valent iron nanoparticles used for environmental remediation with iopromide - Schmid, Doris; Micić, Vesna; Laumann, Susanne; Hofmann, Thilo (Journal of contaminant hydrology, 2015)
The high specific surface area and high reactivity of nanoscale zero-valent iron (nZVI) particles have led to much research on their application to environmental remediation. The reactivity of nZVI is affected by both the water chemistry and the properties of the particular type of nZVI particle used. We have investigated the reactivity of three types of commercially available Nanofer particles (from Nanoiron, s.r.o., Czech Republic) that are currently either used in, or proposed for use in full scale environmental remediation projects. The performance of one of these, the air-stable and thus easy-to-handle Nanofer Star particle, has not previously been reported. Experiments were carried out first in batch shaking reactors in order to derive maximum reactivity rates and provide a rapid estimate of the Nanofer particle's reactivity. The experiments were performed under near-natural environmental conditions with respect to the pH value of water and solute concentrations, and results were compared with those obtained using synthetic water. Thereafter, the polyelectrolyte-coated Nanofer 25S particles (having the highest potential for transport within porous media) were chosen for the experiments in column reactors, in order to elucidate nanoparticle reactivity under a more field-site realistic setting. Iopromide was rapidly dehalogenated by the investigated nZVI particles, following pseudo-first-order reaction kinetics that was independent of the experimental conditions. The specific surface area normalized reaction rate constant (kSA) value in the batch reactors ranged between 0.12 and 0.53Lm(-2)h(-1); it was highest for the uncoated Nanofer 25 particles, followed by the polyacrylic acid-coated Nanofer 25S and air-stable Nanofer Star particles. In the batch reactors all particles were less reactive in natural water than in synthetic water. The kSA values derived from the column reactor experiments were about 1000 times lower than those from the batch reactors, ranging between 2.6×10(-4) and 5.7×10(-4)Lm(-2)h(-1). Our results revealed that the easy-to-handle and air-stable Nanofer Star particles are the least reactive of all the Nanofer products tested. The reaction kinetics predicted by column experiments were more realistic than those predicted by batch experiments and these should therefore be used when designing a full-scale field application of nanomaterials for environmental remediation.
Keywords: kinetika; akrylové pryskyřice; Nanofer; johexol; Nanoparticles; Column reactor; Environmental Restoration and Remediation; voda; koncentrace vodíkových iontů; Iohexol; Česká republika; Acrylic Resins; Batch reactor; železo; poréznost; Water; Czech Republic; Iron; Nanoscale zero-valent iron; Hydrogen-Ion Concentration; Porosity; Kinetics; nanočástice; Iopromide; Reactivity; regenerace a remediace životního prostředí